2008
DOI: 10.1111/j.1529-8817.2008.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH AND CARBON CONTENT OF THREE DIFFERENT‐SIZED DIAZOTROPHIC CYANOBACTERIA OBSERVED IN THE SUBTROPICAL NORTH PACIFIC1

Abstract: To develop tools for modeling diazotrophic growth in the open ocean, we determined the maximum growth rate and carbon content for three diazotrophic cyanobacteria commonly observed at Station ALOHA (A Long-term Oligotrophic Habitat Assessment) in the subtropical North Pacific: filamentous nonheterocyst-forming Trichodesmium and unicellular Groups A and B. Growth-irradiance responses of Trichodesmium erythraeum Ehrenb. strain IMS101 and Crocosphaera watsonii J. Waterbury strain WH8501 were measured in the labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 63 publications
4
74
1
Order By: Relevance
“…Crocosphaera were ~2 days in our incubations, which is comparable to published growth rates 29 . The different levels of 15 …”
Section: Supplementary Online Materials and Figuressupporting
confidence: 89%
“…Crocosphaera were ~2 days in our incubations, which is comparable to published growth rates 29 . The different levels of 15 …”
Section: Supplementary Online Materials and Figuressupporting
confidence: 89%
“…Additionally, Breitbarth et al (2008) find saturation of Trichodesmium IMS101 growth rates at 180 mmol quanta m 22 s 21 (albeit growth was not monitored at irradiances between 50 and 180 mmol quanta m 22 s 21 ). Neither Breitbarth et al (2008) nor Goebel et al (2008) observed photoinhibition within the range of light intensities used in our study (125-500 mmol quanta m 22 s 21 ). Based on these values for growth saturation, each of the light levels used herein is assumed to be sufficient to achieve maximal growth rates.…”
Section: Methodsmentioning
confidence: 45%
“…The light levels used herein (. 125 mmol quanta m 22 s 21 ), the saturation parameters for growth reported by Goebel et al (2008;73 6 29 mmol quanta m 22 s 21 ) and Breitbarth et al (2008), and the statistically similar C fixation rates observed for cultures with similar prior nutritional history indicate that these experiments were all maintained at saturating irradiances. Thus, we can conclude that Trichodesmium IMS101 in well-lit, DIP-deficient conditions can sustain growth rates similar to those achieved with DIP alone via the hydrolysis of P bound in G6P, AMP, MPn, and 2-AEP.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…So far, three groups of unicellular diazotrophic cyanobacteria (UCYN) have been reported in the literature, UCYN-A, B, and C (Zehr et al, 2001;Foster et al, 2007). While UCYN-B and C are nanoplanktonic cells (2 to 10 µm) closely affiliated to the cultivated strains Crocosphaera watsonii and Cyanothece sp., respectively (Church et al, 2005a;Foster et al, 2007), UCYN-A are of picoplanktonic size (0.7-1.5 µm, Biegala and Raimbault, 2008;Goebel et al, 2008) and so far uncultivated. In addition to being freeliving, UCYN have also been suggested to produce mucilage, to attach to inert particles or to live in association with planktonic eukaryotes (Biegala and Raimbault, 2008;Bonnet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%